Flourishing or floundering? Factors contributing to CLIL Primary Teachers' Wellbeing in Austria - Marie-Theres Gruber; Anita Lämmerer; Nicole Hofstadler; Sarah Mercer (Universitat Autònoma de Barcelona, 2020)
CLIL approaches to teaching are part of the general increase in plurilingual approaches to education. Recent work on CLIL in primary education has shown how demanding this can be for teachers. To better understand the nature of these challenges and their potential impact on teacher wellbeing, this study investigated the situation of CLIL primary teachers in Austria. Data were collected via in-depth interviews and coded in an inductive manner using QCAmap software. The analysis of the data revealed that despite considerable individual variation in terms of how CLIL was put into practice, all the wellbeing of all of the teachers' in this study appeared to be threatened by a lack of teaching material, negative public perceptions of teachers generally, low societal appreciation of primary teachers specifically, and language-related challenges in teaching CLIL. In contrast, the teachers' relationships with their students and their conviction in the CLIL approach seemed to contribute positively to their sense of wellbeing in their professional roles. We conclude with some considerations for practice to ensure all primary CLIL teachers flourish in their professional roles.